SPEED CONTROL DESIGN OF THREE PHASE AC INDUCTION MO- TOR USING THE SPACE-VECTOR METHOD AND PROPORTIONAL INTEGRAL CONTROLLER (PI) - Slamet Slamet (Pusbindiklat - LIPI, 2011)
This research described about speed control of three-phase AC induction motor use space vector method and Proportional Integral (PI) controller. To determine the parameters of PI controller used Tuning Charts for PI Feedback Controllers. Measurement of motor speed used dc motor 12 volts functioned as a generator connected by Op-Amp circuit. Output Voltage Op-Amp interfaced to ADC Microcontroller as signal feedback from actual speed of triphase AC induction motor. Then in empiric is searched transfer function of the motor to determine value of the Kp (proportional gain), Ki (integral gain), θ (dead time), and τ (time constant). Testing system is done for set point maneuver from 480 rpm to 1,080 rpm, and then from 1,200 rpm to 480 rpm. Based on the result of research indicates that control system PI for speed of triphase AC motor can be controlled to reach stable condition, if maneuver set point under speciﬁ cation of nominal speed performance of three phasa AC induction motor for 900 rpm.